(untitled) (Boston, MA., 2005)
Case Problems in Finance is a Harvard case course that presents real business situations that pose debatable alternative courses of action. The cases contain problems that can be narrowed but not always settled by the usual techniques of financial analysis. The cases are grouped by major topics: financial analysis and forecasting, cost of capital, working capital management, capital budgeting, dividend policy, debt policy, financial execution, and mergers and restructuring
Keywords: Corporations,Business enterprises; Finance,Case studies,Finance,Case studies